Effect of a short-term psychological intervention on the anxiety and depression of amyotrophic lateral sclerosis patients. (July 2016) - Díaz, José Luis; Sancho, Jesús; Barreto, Pilar; Bañuls, Pilar; Renovell, Mercedes; Servera, Emilio
This study evaluated the effectiveness of a psychological intervention in amyotrophic lateral sclerosis patients, consisting of four semi-structured sessions of cognitive behavioural therapy combined with counselling techniques. An intervention group and a control group were established. The Hospital Anxiety and Depression Scale was used to assess levels of anxiety and depression. In total, fifty-four patients took part. Prior to the intervention, the intervention group displayed rates of 63.3 and 36.7 per cent for anxiety and depression, respectively, falling to 16.7 and 10.0 per cent afterwards. The psychological intervention demonstrated potential for the reduction of levels of anxiety and depression in amyotrophic lateral sclerosis patients.